Large Uterine Fibroids in Pregnancy with Successful Caesarean Myomectomy - Edu Eyong; Okon A. Okon (Case Reports in Obstetrics and Gynecology)
Uterine fibroid is the commonest benign tumour of the female reproductive tract. It occurs in 20–40% of women, whereas the estimated incidence in pregnancy is 0.1–3.9%. Uterine fibroid in pregnancy is usually asymptomatic with complications occurring in 10–30% of cases. The first line of management is conservative with counselling for myomectomy after delivery. However, in the presence of intractable symptoms, both antepartum myomectomy and caesarean myomectomy have been reported to be successfully performed in carefully selected cases. We report a case of large subserous uterine fibroid in pregnancy that was referred to our centre at 14 weeks of gestation. She developed generalized body weakness, backache, and breathlessness at 27 weeks gestation. Thus, she was admitted and managed conservatively for eight weeks with significant relief of symptoms. She eventually had a caesarean myomectomy at 35 weeks of gestation; the outcome was a live female baby with a birth weight of 2.3 kg and a large subserous fibroid weighing 9.5 kg. We can therefore say that caesarean myomectomy can be safely performed in carefully selected cases.